The potentials of agroforestry systems in Denmark and southern Sweden - Yang, Carolina (2020)
In the face of climate change, the urgent need for sustainable food systems has brought agroforestry under the spotlight in the Global North, for its provision of ecosystem services. Despite being less known in the Danish and Swedish context, the traditional practice of managing livestock in the semi-natural pastures, similar to the cut-and-carry systems in the tropics, is undeniably a form of agroforestry system.